Risk and Prevention of Meningococcal Disease among Education Workers: A Review - Philippe De Wals; Pierre Deshaies; Gaston De Serres; Bernard Duval; Lise Goulet; Bernard Pouliot; Sylvie Ricard; Maurice Poulin (Canadian Journal of Infectious Diseases)
The aims of the present study were to review the risk of invasive meningococcal disease (IMD) among education workers, particularly pregnant women, and to evaluate preventive measures, in a context of endemicity, outbreak or epidemic as observed in the province of Quebec. The literature was reviewed and persons in charge of IMD surveillance in France, Quebec, the United Kingdom and the United States were interviewed. Surveys of asymptomatic carriage of Neisseria meningitidis show that transmission among students is higher than transmission between students and teachers. IMD incidence among education workers was analyzed in Cheshire (United Kingdom) in the period from 1997 to 1999, and the results indicated a risk six times higher than that in the general population. Overestimation of the magnitude of the risk is possible because the analysis focused on a cluster. None of the population-based studies of IMD mentioned a risk of secondary cases among education workers. Six IMD cases in education workers were identified in five clusters in schools in the United Kingdom, but not in the other countries. There is no epidemiological study on IMD risk among pregnant women, and this factor was not mentioned in any published review of IMD. Immunization of education workers at the beginning of their employment, using serogroup C glycoconjugate vaccine or a combined A, C, W-135, and Y conjugate vaccine (still under development), could reduce IMD risk, but the cost effectiveness of this measure should be evaluated. The societal benefit of excluding pregnant women from the work place during an outbreak seems to be very low, even if disease risk could be decreased for this specific group. When chemoprophylaxis is indicated for the control of an outbreak in an educational setting, treatment should be offered both to students and teachers in the group at risk.